Manage your workforce ecosystem, not just your employees - Altman, Elizabeth J.; Kiron, David; Schwartz, Jeff 1958-; Jones, Robin (MIT Sloan Management Review, 2023)
Leaders increasingly characterize the workforce as being broader than an organization's employees, encompassing all of the people and groups that contribute to achieving the company's business objectives. The shift is challenging leaders to redefine who and what constitutes their workforce and to develop new management practices and organizational structures.
"Reprint 64433.". - Includes bibliographical references
Keywords: Management; Organizational change; Gestion; Changement organisationnel; management